Knowledge about sudden unexpected death in Parkinson´s disease among speech-language pathologists and audiologists (Research, Society and Development, 2022)
Sudden and Unexpected Death in Parkinson's Disease (SUDPAR) is a sudden and unexpected death without correlated findings at autopsy or in the history of patients with Parkinson's Disease (PD). Our objective was to evaluate the knowledge regarding SUDPAR among Speech-Language pathologists (SLPs) and audiologists in the state of Alagoas, Northeastern Brazil, and to analyze the opinions of these professionals about whether to discuss about the SUDPAR phenomenon with their patients and families. SPLs and audiologists from Alagoas were recruited through an active search on social media, then answered a structured questionnaire with questions about frequency of care for patients with PD; epidemiology and mortality in PD, in addition to questions about SUDPAR. Most SPLs and audiologists (87.2%) did not know about the SUDPAR phenomenon. Among the 26 SPLs and audiologists who knew about SUDPAR, 15 stated that they discuss about the phenomenon with patients and their families/caregivers when asked about the risks related to the possibility of SUDPAR. In conclusion SPLs and audiologists in the state of Alagoas do not know about SUDPAR.